Disciplines en studies. Vernieuwing in de geesteswetenschappen - Tollebeek, Jo (Studium, 2013)
Disciplines and studies. Innovation in the humanitiesThe classic humanities disciplines took shape in the nineteenth century in a complex, contingency- driven process in which factors such as the introduction of a ‘scientific principle’ and the securing of the humanities’ position in the universities played an important role. This process resulted in flexible disciplines that lacked rigidity. For example, there was no ambitious theorising, no development of systematic methodologies and no academic monopoly. This, in turn, made renewal in the humanities a straightforward possibility, particularly when social and cultural changes called for such renewal. The liveliness that characterises teaching and research in the humanities today testifies to this. The renewed demand for cross-disciplinary approaches has led to a number of branches of study (from holocaust and genocide studies to museum studies) which explicitly present themselves as contemporary, focus on a concrete social theme, and often recall a time before the humanities disciplines had emerged in the way that they are organised and function. Anyone wishing to bring stability and continuity to this uneasy pattern of development must take account the factors that reinforced the classic disciplines back then. Among other things, a sustainable policy involves monitoring the quality of the new programmes, relaxed dealings with existing institutional structures and the provision of the necessary seed capital in the field of research.